Mapping the origins of figurative language in comparative literature - Trim, Richard 1950- (Routledge, 2022)
"This book investigates the origins of figurative language in literary discourse within a cognitive framework. It represents an interface between linguistics and literature and develops a 6-tier theoretical model which analyses the different factors contributing to the creation of figurative words and expressions"--Provided by publisher.